Approaches in the utilization of Jatropha Curcas L. as feedstock for biodiesel synthesis: A Review - Ishola, Mohammed Nurudeen; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (2013)
Apprehension about environmental degradation and the diminishing reserve of fossil fuel are the major drives toward search for alternative energy source. Biodiesel of vegetable oils origin such as jatropha curcas oil, possess similar qualities to diesel fuel. Jatropha curcas is considered due to its non-food property, easy propagation, resistant to drought and high yield generation. This paper reviews production routes for biodiesel production utilizing jatropha curcas as feedstock. High conversion is reported in array of routes for jatropha biodiesel synthesis.